A Pilot Study to Determine Penile Oxygen Saturation Before and After Vacuum Therapy in Patients with Erectile Dysfunction After Radical Prostatectomy. (1st April 2014) - Welliver, R. Charles; Mechlin, Clay; Goodwin, Brianne; Alukal, Joseph P.; McCullough, Andrew R.
Abstract: Introduction: Provoked and spontaneous nocturnal erections are thought to play a role in maintenance of male sexual health through oxygenation of the corpus cavernosa. Conversely, hypoxia is thought to be an etiological factor in the pathogenesis of cavernosal fibrosis and long‐term erectile dysfunction. It has been hypothesized that the early penile hypoxia after radical prostatectomy (RP) may lead to fibrosis and consequently a decrease in stretched penile length and long‐term erectile dysfunction. Aim: The aim of this study was to assess the changes in penile tissue oxygenation with vacuum erection device (VED) use. Methods: Twenty men between 2 and 24 months following RP were enrolled prospectively. Each man cycled a VED to achieve full erection 10 consecutive times over a period of approximately 2 minutes without constriction ring. Main Outcome Measures: Tissue oximetry was measured at baseline and immediately after VED using a tissue oximeter at five sites: right thigh, right corpora, glans, left corpora, and left thigh. Additional measurements were captured over the course of an hour. Results: Mean age and time from surgery was 58.2 years and 12.6 months, respectively, and the average Sexual Health Inventory for Men score was 7. Use of the VED significantly increased both glanular and corporal oximetry relative to the baseline values for the entire 60 minutes. An initial increase of 55% was seen in corporal oxygenation with VED use. Conclusions: This is the first study demonstrating that a single, brief application of the VED without a constriction ring results in significant improvement in penile oxygen saturation. The use of a VED has significant benefits for patients both with regard to cost and invasiveness when compared with other penile rehabilitation protocols.